Doubled haploids generated through anther culture from crosses of elite indica and japonica cultivars and/or lines of rice: large-scale production, agronomic performance, and molecular characterization - Grewal, Deepinder; Manito, Christine; Bartolome, Violeta (Wiley, 2011)
We produced 3000 doubled haploid (DH) lines through anther culture of 28 crosses involving indica and japonica rice (Oryza sativa L.) cultivars. Indica cultivars showed low anther culturability (1.2% callus induction) whereas japonica cultivars had 20‐fold higher (28.1%) anther culturability. A set of 121 and 124 DH lines was used for phenotypic and molecular analysis, respectively, generated from the japonica cultivar (IR69428) × indica variety (IR64). Significant variation was observed among DH lines for agronomic traits including Zn content. However, the phenotypic variance within each DH line was comparable with the mean phenotypic variance of the parents, suggesting no variation within DH line(s). A set of 209 simple sequence repeat (SSR) markers was selected to construct a linkage map with a total genetic distance of 2148.8 cM. Simple sequence repeat analysis showed 1:1 ratio of indica and japonica alleles. Of the 209 markers, 21 showed distorted segregation and these markers are randomly located over 12 chromosomes. Homozygosity was detected for all the marker loci in 124 DH lines and 28 were heterozygote. Results show that indica cultivars are recalcitrant and genes for anther culturability are partially dominant. Molecular and phenotypic trait analysis of the DH lines showed that the origin of DHs is from pollen and these 121 DH lines are thus a valuable genetic resource in mapping quantitative trait loci (QTL) for grain Zn content and other agronomic traits. Interestingly, some of the DH lines had indica traits and high (28.3 mg kg−1) grain Zn content in polished rice.